The Western Balkans: A Higher Education Problem Area - Temple, Paul (International Higher Education, 2013)
The summer 2012 issue of International Higher Education (no. 68) included articles on higher education in two countries from the former Yugoslavia—Philip G. Altbach on Slovenia and Stamenka Uvalic-Trumbic on Serbia—and a review of developments in another Balkan country—Romania, by Paul Serban Agachi. The picture that emerges from these reviews is of higher education systems with undoubted strengths, struggling to overcome dysfunctional historical legacies, dating from before and after the formally communist period, but certainly strongly conditioned by it. It may be worthwhile to compare the situations reported in these countries, with those found across the countries of the fragmented region now known as the Western Balkans—Albania, Bosnia-Herzegovina, Macedonia, and Montenegro, as well as Serbia.